PREDICTING CONSUMER LOYALTY TO ONLINE TAXI SERVICES USING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Lifianto, Panji Pratama; Ferbruadi, Agustinus (Faculty of Economic and Business, University of Pasundan, 2023)
This study aims to measure the factors that can affect customer loyalty in using the mobile taxi service application using the Technology Acceptance Model (TAM). The research model used involves several variables, namely perceived usefulness, perceived ease of use, attitude, customer loyalty and customer satisfaction as additional variables. The analysis used was Structural Equation Modeling (SEM) and respondents numbered 105 people from the city of Bandung. This research proves that in addition to the variables contained in the Technology Acceptance Model (TAM), in achieving loyalty the users of the mobile taxi service application must achieve customer satisfaction first. The results of this study indicate that the presence of customer satisfaction as an additional variable can increase understanding in technology acceptance by completing variables that are part of the Technology Acceptance Model (TAM).